The impact of absorbed photons on antimicrobial photodynamic efficacy - Fabian eCieplik; Andreas ePummer; Johannes eRegensburger; Karl-Anton eHiller; Andreas eSpäth; Laura eTabenski; Wolfgang eBuchalla; Tim eMaisch (Frontiers in Microbiology, 2015)
Due to increasing resistance of pathogens towards standard antimicrobial procedures, alternative approaches that are capable of inactivating pathogens are necessary in support of regular modalities. In this instance, the photodynamic inactivation of bacteria (PIB) may be a promising alternative. For clinical application of PIB it is essential to ensure appropriate comparison of given photosensitizer (PS)-light source systems, which is complicated by distinct absorption and emission characteristics of given PS and their corresponding light sources, respectively.Consequently, in the present study two strategies for adjustment of irradiation parameters are evaluated: (i) matching energy doses applied by respective light sources (common practice) and (ii) by development and application of a formula for adjusting the numbers of photons absorbed by PS upon irradiation by their corresponding light sources. Since according to the photodynamic principle one PS molecule is excited by the absorption of one photon, this formula allows comparison of photodynamic efficacy of distinct PS per excited molecule.In light of this, the antimicrobial photodynamic efficacy of recently developed PS SAPYR was compared to that of clinical standard PS Methylene Blue (MB) regarding inactivation of monospecies biofilms formed by Enterococcus faecalis and Actinomyces naeslundii whereby evaluating both adjustment strategies.PIB with SAPYR exhibited CFU-reductions of 5.1 log10 and 6.5 log10 against E. faecalis and A. naeslundii, respectively, which is declared as a disinfectant efficacy. In contrast, the effect of PIB with MB was smaller when the applied energy dose was adjusted compared to SAPYR (CFU-reductions of 3.4 log10 and 4.2 log10 against E. faecalis and A. naeslundii), or there was even no effect at all when the number of absorbed photons was adjusted compared to SAPYR. Since adjusting the numbers of absorbed photons is the more precise and adequate method from a photophysical point ..